1999
DOI: 10.1210/en.140.8.3805
|View full text |Cite
|
Sign up to set email alerts
|

Estrogen Receptor-  Detected on the Plasma Membrane of Aldehyde-Fixed GH3/B6/F10 Rat Pituitary Tumor Cells by Enzyme-Linked Immunocytochemistry

Abstract: A population of estrogen receptor-alpha (ER alpha) proteins, located at the plasma membrane, is postulated to mediate the rapid, nongenomic responses of GH3/B6/F10 pituitary cells to estrogen. To demonstrate the presence of ER alpha at the plasma membrane and to distinguish this receptor population from that in the nucleus, GH3/B6/F10 cells were first prepared in 2% paraformaldehyde/0.1% glutaraldehyde in PBS (P/G) without detergent, then exposed to one of several antibodies (Abs) raised against nuclear ER alp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
86
1

Year Published

1999
1999
2008
2008

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 105 publications
(96 citation statements)
references
References 0 publications
9
86
1
Order By: Relevance
“…n.d., not done. a, Norfleet et al 1999a;b, Norfleet et al 1999b;c, Pappas et al 1995a;d, Pappas et al 1995b;e, Pappas et al 1994;f, Watson et al 1995. results from these experiments are summarized in Fig. 1, which depicts recognition of seven epitopes by nine antibodies to iERá.…”
Section: ------------------------------------------------------------mentioning
confidence: 92%
“…n.d., not done. a, Norfleet et al 1999a;b, Norfleet et al 1999b;c, Pappas et al 1995a;d, Pappas et al 1995b;e, Pappas et al 1994;f, Watson et al 1995. results from these experiments are summarized in Fig. 1, which depicts recognition of seven epitopes by nine antibodies to iERá.…”
Section: ------------------------------------------------------------mentioning
confidence: 92%
“…A number of immunocytochemical studies have demonstrated that antibodies to ERα will bind to the exterior of the cell. Watson and colleagues have shown that seven different antibodies to ERα bind to the membrane of rat pituitary tumor cells and antibodies that bind to the hormone-binding domain of ERα modulate rapid E-induced prolactin release [94]. In the hippocampus estradiol regulates the subcellular distribution of phosphorylated Akt in hippocampal CA1 dendrites [143] and there is ultrastructural evidence that there are ERα .…”
Section: Mechanisms Mediating the Effects Of Estradiol On The Striatumentioning
confidence: 99%
“…This case has been confirmed in other nuclear receptor such as estrogen receptor α (ERα). In ERα-expressing pituitary tumor cells (GH3 cells), ERα is located in the plasma membrane and mediates the estrogen-induced rapid release of prolactin, because it is blocked or stimulated directly by antibodies directed to different amino acid sequences of ERα [32].…”
Section: Rapid Glucocorticoid Actions Via Membrane Receptorsmentioning
confidence: 99%